The Influences of Intergroup Relations on an Organizational Structure - Varol, Nurhayat; Varol, Serkan (Acad Conferences Ltd, 2012)
Organizational structures have been used for centuries. It started from the early days of first age. One man would be given the task of leading the whole group and assigning tasks to each member of his team. Overall, an organizational structure consists of activities such as supervision, allocation and coordination which work for the achievement of organizational aims. Groups in organizations are not just made of a dozen employees. There are subtasks and subunits that really form the group. The way we are defining group and the characteristics we understand has been an ongoing debate for many years. Group can be described as work teams, subpart of departments or any organization members that value the existence of each other. There are two groups available in organizations. They are formal and informal groups. Under formal group, there are two subgroups; permanent and temporary formal, depending on the needs of the organizations where the rules and targets are clearly determined and given in a written format. Informal group consists of a small number of people who actively participate in activities and take active roles in sharing feelings for the purpose of the meeting. Group and intergroup relations have become an important concept for the discipline of social psychology, conflict resolution and group decision making. Most likely, intergroup relations are the ones that are influenced by the social identities and perceptions of groups. Thus, intergroup relations are becoming more problem for organizations. It is also believed that the quality of intergroup relations show the characteristic of the organization. As population increases along with technological advancements and economic volatility, the nature relation between group members can be altered, When intergroup relations are harmonious; members of different groups will be less sensitive about differences between in-groups and out-groups. However, when there is a conflict, identification with one's group becomes stronger, out-group differences can become more obvious where intergroup conflict increases. The intergroup relations in the universities and within the departments of the universities are crucial. Team and group working influences the educational efficiency of the department. However, it may yield more ambiguity when this relations shape the organizational structure of the university. In this study, intergroup relations within the universities in Turkey are investigated. A survey is applied to the faculty, staff and students to find the positive and negative effects of the intergroup relations on the university, quality of the education, and faculty performance. Finally, some recommendations are submitted using findings of the survey.
9th International Conference on Intellectual Capital, Knowledge Management and Organisational Learning (ICICKM) -- OCT 18-19, 2012 -- Univ Rosario, Bogota, COLOMBIA
Keywords: group influence to the organization; intergroup relations; organizational structure